1997
DOI: 10.1017/s0889189300007244
|View full text |Cite
|
Sign up to set email alerts
|

Alternative production systems' effects on the K-factor of the Revised Universal Soil Loss Equation

Abstract: The soil erodibility factor (K) of the Revised Universal Soil Loss Equation is currently considered a constant for all soils in the same type, regardless of production practice. To examine the effect of alternative production systems on the K-factor we compared pairs of alternatively and conventionally farmed fields on a Judson silt loam (Fine-silty, mixed, mesic Cumulic Hapludolls), a Yutan silty clay loam (Fine-silty, mixed, mesic Mollic Hapludalf), and a Wann fine sandy loam (Coarse-loamy, mixed, mesic Fluv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Most of those studies are based on models such as the Universal Soil Loss Equation (USLE, empirical) or the Water Erosion Prediction Project (WEPP, process-based) (Lockeretz et al 1981;Reganold 1988;Auerswald et al 2003;Pacini et al 2003;Arnhold et al 2014). Some studies indirectly assessed soil erosion by evaluating topsoil thickness (Reganold et al 1987), soil erodibility (Fleming et al 1997;Siegrist et al 1998;Kuhn et al 2012), aggregate stability (Mulla et al 1992;Pulleman et al 2003), or nutrients in runoff of farm drainage systems (Eltun et al 2002) and one study directly assessed soil erosion in organically versus conventionally managed plots (Weilgart Patten 1982) using the Alutin rill method. Even if it can be stated that erosion models have originally been calibrated with field data, there is a general lack of experimental in situ measurements to compare organic farming systems (Gomiero 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most of those studies are based on models such as the Universal Soil Loss Equation (USLE, empirical) or the Water Erosion Prediction Project (WEPP, process-based) (Lockeretz et al 1981;Reganold 1988;Auerswald et al 2003;Pacini et al 2003;Arnhold et al 2014). Some studies indirectly assessed soil erosion by evaluating topsoil thickness (Reganold et al 1987), soil erodibility (Fleming et al 1997;Siegrist et al 1998;Kuhn et al 2012), aggregate stability (Mulla et al 1992;Pulleman et al 2003), or nutrients in runoff of farm drainage systems (Eltun et al 2002) and one study directly assessed soil erosion in organically versus conventionally managed plots (Weilgart Patten 1982) using the Alutin rill method. Even if it can be stated that erosion models have originally been calibrated with field data, there is a general lack of experimental in situ measurements to compare organic farming systems (Gomiero 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The mitigation of runoff, erosion and crop losses as a result of rainfall excess, a serious agricultural constraint (Jaenicke, 1998;USDA, 1994), is also improved in organically managed systems. Organic management of soils leads to improved soil stability and resistance to water erosion compared to conventionally managed soils, due to higher soil C content and improved soil aggregation (Clark et al, 1998;Drinkwater et al, 1995;Liebig and Doran, 1999;Reganold, 1995;Reganold et al, 1993), permeability (Fleming et al, 1997;Gerhardt, 1997;Petersen et al, 1999;Reganold et al, 2001) and lower bulk density (Gerhardt, 1997;Liebig and Doran, 1999;Reganold et al, 1993), as well as higher resistance to wind erosion (Jaenicke, 1998). Comparisons of erosion rates in organic versus conventional systems, show significantly lower erosion in organically managed systems.…”
Section: Introductionmentioning
confidence: 99%
“…Lockeretz et al (1981) reported one-third less erosion from Midwest organic farms than from comparable conventionally managed farms. Fleming et al (1997) showed that the K-factor (soil erodibility) of the revised universal soil loss equation was reduced in organically managed systems.…”
Section: Introductionmentioning
confidence: 99%